(Photo)electrochemical Methods for the Determination of the Band Edge Positions of TiO2-Based Nanomaterials. (9th February 2012) - Beranek, Radim
Abstract : TiO2 -based nanomaterials play currently a major role in the development of novel photochemical systems and devices. One of the key parameters determining the photoactivity of TiO2 -based materials is the position of the band edges. Although its knowledge is an important prerequisite for understanding and optimizing the performance of photochemical systems, it has been often rather neglected in recent research, particularly in the field of heterogeneous photocatalysis. This paper provides a concise account of main methods for the determination of the position of the band edges, particularly those suitable for measurements on nanostructured materials. In the first part, a survey of key photophysical and photochemical concepts necessary for understanding the energetics at the semiconductor/solution interface is provided. This is followed by a detailed discussion of several electrochemical, photoelectrochemical, and spectroelectrochemical methods that can be applied for the determination of band edge positions in compact and nanocrystalline thin films, as well as in nanocrystalline powders.